Strengthening policy analysis: econometric tests using microcomputer software - Haddad, Lawrence J.; Westbrook, M. Daniel; Driscoll, Danie; Payongayong, Ellen; Rozen, Joshua; Weeks, Melvyn (International Food Policy Research Institute, 1995)
"This ... is a manual outlining how to conduct some fairly basic econometric tests and procedures to determine the robustness of the estimated parameters upon which policy decisions are frequently based. ...[It] address[es] a number of issues relating to the choice of model variables, the choice of estimation method, and the sensitivity of results to missing or extreme data values"--P. vii.